Effectiveness of Web-Based Interactive Thematic Map Media in Enhancing Students’ Chronological and Geospatial Thinking in History Learning - Norman Setiyadi; Kurniawati Kurniawati; Fakhruddin Fakhruddin (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
This study aims to examine the effectiveness of web-based interactive thematic map media in improving students’ chronological and geospatial thinking skills in history learning. The research employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The participants consisted of 78 eleventh-grade students at SMAN 1 Cijeruk, divided into an experimental group and a control group. Data were collected through pretest and posttest using a validated and reliable multiple-choice instrument. Data analysis was conducted using nonparametric statistical tests, including the Mann–Whitney U-Test and Wilcoxon Signed-Rank Test. The findings indicate that there was no significant difference in students’ initial abilities between the experimental and control groups. However, after the treatment, the experimental group showed significantly higher posttest scores compared to the control group (p < 0.05). Both groups experienced improvement, but the increase was more substantial in the experimental group. The N-Gain analysis revealed a moderate level of effectiveness (0.64), indicating that the use of interactive thematic map media contributed positively to students’ learning outcomes. These results suggest that web-based interactive thematic map media is effective in enhancing students’ chronological and geospatial thinking skills. The integration of visual and interactive elements enables students to better understand historical events in terms of time sequence and spatial context, thereby improving both conceptual understanding and analytical thinking in history learning.